Microwave-assisted synthesis of palladium-based core-shell nanocatalysts and iron phthalocyanines and their applications in direct alkaline alcohol fuel cells - Ozoemena, Kenneth I. (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2013.